Analysis of Community Resilience Factors in One Area Against Flood Disasters - Andie; Sutrisno, Herwin; Permana, Indrawan; Susi, Theresia; Perkasa, Petrisly (Green Publisher Indonesia, 2025)
Floods that impact residential areas can disrupt urban activities and significantly affect the lives of people residing in flood-prone zones. The Flamboyan Bawah settlement in Langkai village, Jekan Raya sub-district, Palangka Raya city is one such area frequently affected by flooding. Nevertheless, residents continue to choose to remain in the area. Therefore, this research aims to analyze the factors influencing community resilience in a specific area against flood hazards, with a focus on Palangka Raya. A mixed-methods design, integrating both quantitative and qualitative approaches, was employed. Data collection involved observations, interviews, questionnaires, and document analysis, with a sample comprising 100 heads of households. Multiple linear regression was utilized for data analysis. The results indicate that social factors, economic factors, physical aspects of housing, and policy factors all have a positive and significant influence on community resilience. This finding suggests that resilience in flood-prone communities is not determined by a single factor, but rather by the interaction of multiple dimensions. Communities tend to persist due to strong social capital, established economic adaptation strategies, housing modifications tailored to environmental conditions, and support from government policies. The implications of this study highlight the need for more adaptive policy planning, improvements in housing quality, strengthening of the local economy, and enhancement of social capacity within communities to increase resilience to flood risks in vulnerable areas.